Methodology Principles of Mathematical Training of Vocational Teachers - Y. A. Perminov (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the methodology aspects of the mathematical course modernization in the context of prospective vocational teachers' training. The author defines the basic pedagogical principles of mathematical training in vocational pedagogic universities - the fundamentality, binary character, leading idea principle and continuity. The link between mastering the mathematical discipline and methodology competence development is substantiated. The author points out that the content and methodology of vocational teachers' training should be modified because of the intensive implementation of mathematical apparatus in all scientific and professional spheres. The education related sciences (didactics, psychology, sociology, etc.) started using such mathematical methods as statistics, discrete mathematics, mathematical modeling etc. Therefore, the methodology of vocational training re- quires from pedagogical students a good command of mathematical language and later on its adaptation and application in teaching the professional disciplines.